Factors Leading to Successful Performance on U.S. National Licensure Exams for Medical Students: A Scoping Review - Jeyaraju, Maniraj; Linford, Henry; Mendes, Thiago Bosco [UNESP]; Caufield-Noll, Christine; Tackett, Sean (Oxford University Press (OUP), 2023)
Purpose: To synthesize the evidence of the factors leading to successful performance on knowledge-based national licensure exams (NLEs) for medical students. Method: The authors conducted a scoping review to summarize the peer-reviewed empiric literature that used United States Medical Licensing Examination (USMLE) Step 1 or Step 2 Clinical Knowledge or Comprehensive Osteopathic Medical Licensing Examination (COMLEX) Level 1 or Level 2 Cognitive Evaluation scores as outcomes. The authors searched PubMed and Scopus without date restrictions through April 30, 2021. Two reviewers independently screened and selected studies for inclusion. Data were summarized narratively and with descriptive statistics. Results: The authors screened 1,185 unique citations and included 233 full-text studies in their review. Of these, 201 (86%) were studies of USMLE exams, 31 (13%) were studies of COMLEX exams, and 1 (0.4%) reported on both. The authors classified 29 studies (12%) as informing NLE preparation, 163 (70%) as attempting to identify predictive variables, and 76 (33%) as using NLE scores for program evaluation. Preparation studies found that the number of practice test items, practice exam scores, and less time in dedicated preparation correlated with higher NLE scores. Use of other commercial resources or study strategies was not consistently associated with higher scores. Predictive studies found the strongest relationships between individuals' performance on past assessments and their NLE scores. Conclusions: The factors leading to successful performance on knowledge-based NLEs align with well-known principles from the cognitive sciences. Learners build on existing foundations of knowledge (reflected in their prior academic performance) and are likely to learn more efficiently with testing and spaced learning over time. While commercial test preparation resources are ubiquitous, there is no evidence that a single resource gives students a competitive advantage on NLEs. Developing habits of regular and continuous learning is necessary for clinical practice and successful NLE performance.